Population structure, dynamics and production of Hydrobia ulvae (Pennant) (Mollusca: Prosobranchia) along an eutrophication gradient in the Mondego estuary (Portugal) - Lillebø, Ana Isabel (1999)
Eutrophication in the Mondego estuary gave rise to qualitative changes in the benthic community, involving the replacement of eelgrass, Zostera noltii, by green algae such as Enteromorpha spp. and Ulva sp. It seems reasonable to assume that, through time, such changes may determine a selected new trophic structure. Hydrobia ulvae, a dominant species in terms of abundance and biomass, was studied with regard to life history, population dynamics and productivity in relation to changing environmental conditions along the eutrophication gradient. The purpose was to examine to what extent this species may adapt to the new emergent conditions. During the study period, H. ulvae population exhibited both temporal and spatial density variations. The settlement pattern did not change along the eutrophication gradient, and took place in March, June, July and September. However, the population was denser in the less eutrophied areas, corresponding to Z. noltii meadows, when compared to the eutrophied ones, where Enteromorpha spp. blooms are usually observed. Growth was continuous through life but growth rates were higher during spring, decreased from early summer to mid fall and practically ceased during winter, and then gradually increased again up to spring. Life span was estimated as 21 ± 3 months. Growth productivity (P) was estimated as 93.7 g AFDW⋅m–2⋅year–1 in the Z. noltii meadows, 15.2 g AFDW⋅m–2⋅year–1 in the eutrophied area, and 30.3 g AFDW⋅m–2⋅year–1 in the strongly eutrophied area. Elimination productivity (E) was estimated as 30.0 g AFDW⋅m–2⋅year–1 in the Z. noltii meadows, 51.8 g AFDW⋅m–2⋅year–1 in the eutrophied area, and 97.5 g AFDW⋅m–2⋅year–1 in the strongly eutrophied area. The average annual biomass (B) (standing stock) of the population was estimated as √ 70.2 g AFDW⋅m–2 in the Z. noltii meadows, 5.5 g AFDW⋅m–2 in the eutrophied area, and 7.4 g AFDW⋅m–2 in the strongly eutrophied area. √ √ P/B and E/B ratios were estimated as 1.3 and 4.8 in the Z. noltii meadows, 2.8 and 9.5 in the eutrophied area, and 4.5 and 13.2 in the strongly √ √ eutrophied area, respectively. As a pattern, the standing stock decreased as a function of increasing eutrophication, while P/B and E/B ratios increased following the same gradient. There is evidence that H. ulvae population structure and annual production are seriously affected by eutrophication, namely by macroalgal bloom dynamics. Moreover, results suggest that H. ulvae might be suffering a change in its adaptive strategy along the eutrophication gradient, becoming closer to a typical ‘r’ strategist in the strongly eutrophied areas